Black Hammer : streets of spiral - Lemire, Jeff; Brombal, Tate; Fawkes, Ray (Dark Horse Books, 2019)
"Collects Black Hammer: Giant Sized Annual, Black Hammer: Cthu-Louise, World of Black Hammer, and Material from Free Comic Book Day 2019"--